2014
DOI: 10.1002/pros.22787
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease inhibitor Kazal type 1 promotes epithelial-mesenchymal transition through EGFR signaling pathway in prostate cancer

Abstract: These findings suggest that SPINK1 promotes EMT through EGFR signaling pathway in PCa and SPINK1 could be a new prognostic marker in Chinese PCas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Later, Leinonen et al [20] reported that SPINK1 expression is associated with aggressive form of the disease and could serve as a biomarker in endocrine-treated PCa patients. In consistent with these findings, our results revealed that SPINK1 overexpression is an unfavorable prognostic factor in Chinese PCa patients [21].…”
Section: Prognostic Association Of Spink1 Overexpressionsupporting
confidence: 90%
See 2 more Smart Citations
“…Later, Leinonen et al [20] reported that SPINK1 expression is associated with aggressive form of the disease and could serve as a biomarker in endocrine-treated PCa patients. In consistent with these findings, our results revealed that SPINK1 overexpression is an unfavorable prognostic factor in Chinese PCa patients [21].…”
Section: Prognostic Association Of Spink1 Overexpressionsupporting
confidence: 90%
“…these studies, we also suggested SPINK1 is mutually exclusive with ERG rearrangement status in Chinese PCa patients and the prevalence of SPINK1 overexpression is comparable with that of western populations [21]. In contrast, some previous reports did not find such mutual exclusivity, although the majority of which suggested the incidence rate was very low for concomitance of SPINK1 and ETS fusions [20,22].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…A more recent study conducted with RWPE cells showed that SPINK1-induced increase in motility was associated with epithelial-mesenchymal transition (EMT) (36 ). Correlating with the results from pancreatic cancer studies, EGFR and MAPK inhibitors were able to reverse the invasive capacity of prostate cancer cells, suggesting that SPINK1-induced EMT was mediated by the EGFR-MAPK signaling pathway (36 ).…”
Section: Prostate Cancermentioning
confidence: 93%
“…A majority of the oncogenic functions of SPINK1 seem to be mediated by the MAPK pathway (27,36,59,66 ). Current US Food and Drug Administration-approved targeted therapies include the RAF inhibitor sorafenib for treatment of kidney, liver, and thyroid cancer; the MEK inhibitor trametinib for treatment of melanoma; and the EGFR, ERK1/2, and Akt inhibitor lapatinib for treatment of breast cancer.…”
Section: Potential Use Of Spink1 As a Therapeutic Target In Cancermentioning
confidence: 99%